The use of cross-flow membrane emulsification to fabricate large, porous polymeric microparticles for tissue engineering applications - Chowdhury, Sanchita Sharmin (2017)
A common approach in tissue engineering strategies is to deliver living cells together with supporting scaffolds to damaged or injured body parts and then induce cell proliferation and differentiation for the purpose of regenerating functional tissues. Porous polymeric microparticles (Por-MPs), as scaffolds have recently received extensive interest for their pores, facilitating exchange of nutrients throughout the scaffolds and, sizes ( micrometre scale) and shapes (spherical), offering delivery of the cell-scaffold system via narrow bore needle with minimally invasive surgical intervention to repair irregularly shaped tissue defect. For fabrication of MPs, conventional emulsion-solvent evaporation (CE) methods are most commonly used; however the size distributions of the prepared MPs are broad, which could bring negative impacts on the efficiency of the scaffolds as cell-delivering vehicles. On the other hand, cross-flow membrane emulsification (X-ME) is a promising technique for preparation of uniform-sized MPs.